Determinants of pelvic organ prolapse among adult gynecologic patients in Mekelle University Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia: Case control study design - Birhane Mekonen; Solomon Hintsa; Hailay Syum; Dawit Zenebe; Gebretsadik Kiros Lema; Ainom Shimondi; Redaie Girmay; Freweyni Fisshatsion; Goitom Girmay (PLoS ONE, 2025)
Background Pelvic organ prolapse is a major cause of morbidity among women in both high-income and low-income countries. Despite the severity of the problem, the risk factors associated with pelvic organ prolapse has been poorly understood in Ethiopia mainly in the study area. Hence, the purpose of this study was to identify determinants of pelvic organ prolapse among adult gynecologic patients at Mekelle University Ayder Comprehensive Specialized Hospital. Objective To identify determinants of pelvic organ prolapse among adult gynecologic patients in Mekelle University Ayder Comprehensive Specialized Hospital, Tigray, Ethiopia, 2024. Methods Hospital-based case-control study design was conducted from March 01, 2024 to May 30, 2024. All cases diagnosed with pelvic organ prolapse were enrolled in the study. Then, 4:1 control-to-cases ratio was applied. Data were entered into Epi Data version 4.6 and analyzed using SPSS version 21. Figures and tables were used for descriptive statistics. Variables with P-value less than 0.2 during binary logistic regression were labeled as candidates for multivariable logistic regression to identify independent predictors of pelvic organ prolapse at p-value < 0.05. The overall model fitness was checked by Hosmer Lemeshow at a P-value > 0.05. Finally, variables with P-value less than 0.05 and a 95% confidence interval of adjusted odds ratio were considered significant factors for the determinants of pelvic organ prolapse. Results A total of 478 participants were recruited with a 100% response rate for both cases and controls. Low income (AOR=3.3; 95% CI: 1.1–9.7), vaginal tear (AOR=6.6; 95% CI: 2.5–17.6), menopausal status (AOR=9.2, 95% CI:2.3–37.4), body mass index <18 kg/m2 (AOR=6.3, 95% CI: 2.7–14.4), body mass index ≥25 (AOR= 5.6, 95% CI: 1.5–21.2) and chronic constipation (AOR=6.4, 95% CI: 2.9–13.9) were identified as determinants of pelvic organ prolapse. Conclusions In this study, income of the participant, vaginal tear, menopausal status, body mass index (both underweight and overweight), and chronic constipation were factors found to be significantly associated with pelvic organ prolapse. Therefore, creating awareness about risk factors of pelvic organ prolapse, screening and early intervention, weight management program, and hormonal support is recommended.